Effects of Nutrient and Water Supply During Fruit Development on Metabolite Composition in Tomato Fruits (Solanum lycopersicum L.) Grown in Magnesium Excess Soils - Kim, Yangmin X.; Kwon, Min Cheol; Lee, Seulbi; Jung, Eun Sung; Lee, Choong Hwan; Sung, Jwakyung (Frontiers in Plant Science, 2020)
Tomato cultivation in the greenhouse or field may experience high surplus salts, including magnesium (Mg2+), which may result in differences in the growth and metabolite composition of fruits. This study hypothesized that decreasing the supply of nutrients and/or water would enhance tomato fruit quality in soils with excess Mg2+ that are frequently encountered in the field and aimed to find better supply conditions. For tomato plants cultivated in plastic pots using a plastic film house soil, the fertilizer supply varied in either the nitrogen (N) or potassium (K) concentration, which were either 0.1 (lowest) or 0.75 times (lower) than the standard fertilizer concentrations. Water was supplied either at 30 (sufficient) or 80 kPa (limited) of the soil water potential. Lycopene content on a dry-weight basis (mg/kg) was enhanced by the combination of lowest N supply and sufficient water supply. However, this enhancement was not occurred by the combination of the lowest N supply and limited water supply. Sugars and organic acids were decreased by limiting the water supply. Therefore, we carefully suggest that an adjustment of nitrogen with sufficient watering could be one of strategies to enhance fruit quality in excess Mg2+ soils.